Evaluación del Sistema Tributario Nacional para establecer propuestas del incremento de la base tributaria. - Lázaro Ruíz, Javier Ricardo (2012)
The present investigation work was developed with the intention of sketching our posture in the face of a critical reality, and as professionals in the countable sciences to establish proposals of Increment of the Tributary Base. The National Tributary System is regulated through the Ordinance Legislative number 771 Law Marco of the National Tributary System. The National Tributary System is based on three strategic lines as they are: the execution control, facilitation of the execution and the fight against the tributary nonfulfillment. It is conformed by the tax to the rent, the General Tax to the Sales, the Selective Tax to the Consumption, the tariff rights, the municipal tributes and the contributions to the Public Health and the state system of pensions administered by the Office of Normalization of Forecast. The Tributary Code is the norm rector of the principles, institutions and juridical norms that inspire to the Right Tributary Peruvian. It is necessary to indicate that in spite of their transcendency for the Tributary Right, the Tributary Code doesn't regulate a tribute especially and as such, technically speaking, it is not part of the National Tributary System. The tributary escape that today in day has become a complex and difficult socio-economic phenomenon, it has existed from all the times, and the most serious is that not alone it generally means a loss of fiscal revenues whose effect is notorious in the faulty or limited benefit of public services, but rather it also rebounds in a distortion of the national tributary system. Before the formulation of proposals to achieve the increment of the tributary base, we will focus the problematic reality, the objectives and we will formulate the respective conclusions and recommendations. By means of the present investigation work it is looked for the economic benefits that are obtained of the collection function that he/she carries out the National Superintendence of Tributary Administration and Customses through the methods implemented by this entity to settle down. The methods that he/she carries out the administration inside the abilities of determination and inspection specified in the Book Second of the Orderly Unique Text of the Tributary Code, are: Procedure of Coercive Collection, Contentious Procedure - Tributary, non Contentious Procedure. The National Tributary System should be guided to collect the tributes in an effective and efficient way achieving this way the escape, to avoid to pay of legal form and the smuggling.